UGT1A1 Variants c.864+5G>T and c.996+2_996+5del of a Crigler-Najjar Patient Induce Aberrant Splicing in Minigene Assays - Gailite, Linda; Valenzuela-Palomo, Alberto; Sanoguera-Miralles, Lara; Rots, Dmitrijs; Kreile, Madara; Velasco, Eladio A. (Frontiers in Genetics, 2020)
A large fraction of DNA variants impair pre-mRNA splicing in human hereditary disorders. Crigler-Najjar syndrome (CNS) is characterized by a severe unconjugated hyperbilirubinemia caused by variants in the UGT1A1 gene. We previously reported one CNS-type II patient with two splice-site variants (c.864+5G>T and c.996+2_996+5del). According to MaxEntScan, both disrupt their corresponding donor sites (c.864+5G>T: 6.99→2.28; c.996+2_996+5del: 5.96→ -11.02), so they were selected for subsequent functional tests. Given the unavailability of patient RNA, we constructed an UGT1A1 splicing-reporter minigene with exons 1-4 to characterize the underlying splicing anomaly. The variant c.996+2_996+5del generated two aberrant transcripts, ∆(E2) (exon 2 skipping/64%) and ▼(E2q135) (intron retention of 135-nt/36%), which lead to the loss of 20 conserved amino-acids and the gain of 45 new ones of a critical functional domain, respectively. The c.864+5G>T variant mainly produced the aberrant transcript ∆(E1q141) (141-nt deletion/70.4%) and the full-length isoform (29.6%). ∆(E1q141) would provoke the loss of 47 amino-acids of the N-terminal domain that encodes for substrate specificity. Thus, the three anomalous transcripts are likely to inactivate UGT1A1. Moreover, this patient is also homozygous for the promoter variant A(TA)7TAA that decreases UGT1A1 expression by 70%, so the full-length transcript produced by c.864+5G>T would be even more reduced (<9%), thus supporting the diagnosis of CNS-type II. Therefore, minigenes represent valuable tools for the functional and clinical classifications of genetic variants.